2016
DOI: 10.4187/respcare.04436
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Inductance Plethysmography Improved Diagnostic Sensitivity and Specificity of Obstructive Sleep Apnea

Abstract: BACKGROUND: Respiratory inductance plethysmography (RIP) is a tool used during a polysomnogram (PSG), which serves as a surrogate of respiratory effort and can help detect inspiratory air-flow limitation. We hypothesize that RIP can improve the sensitivity and specificity of scoring hypopneas when compared with both the recommended and acceptable criteria of the American Academy of Sleep Medicine. METHODS: We retrospectively analyzed a cohort of 12 subjects who had no obstructive sleep apnea (OSA) or mild OSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
1
13
0
1
Order By: Relevance
“…Putting the attention on circumferential changes, which are basically as well a distance change or expansion, then, due to the dynamic character and circular arrangement and the large dimension of these changes (changes up to 100 mm and more), their determination requires a special measuring principle. These dynamic circumferential changes of the upper body can be determined inductively, for example in RIP [ 35 ], by textile strain gauges [ 36 ], or by optical encoders via CiMeD belts [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Putting the attention on circumferential changes, which are basically as well a distance change or expansion, then, due to the dynamic character and circular arrangement and the large dimension of these changes (changes up to 100 mm and more), their determination requires a special measuring principle. These dynamic circumferential changes of the upper body can be determined inductively, for example in RIP [ 35 ], by textile strain gauges [ 36 ], or by optical encoders via CiMeD belts [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Severe OSA is defined by ≥30 apneic or hypopneic events per hour (AASM, 1999) and individual events can range from 10 seconds (the minimum duration to be counted) to over 60 seconds (Leppanen et al, 2016). The struggle phase in volitional apnea and obstructive apnea is generally defined with inductance plethysmography (e.g., (Kogan et al, 2016)), however, this technique indirectly assesses respiratory effort. Berry and colleagues demonstrated chest wall electromyographic (EMG) signals associated with the electrocardiogram (ECG) were useful in defining periods of obstructive sleep apnea (Berry et al, ,,2016(Berry et al, ,, , 2018(Berry et al, ,, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the accuracy of RR measurements using strain gauge sensors changes with different body locations [18], [19]. However, the majority of existing studies on RR monitoring accuracy were focused at two common locations namely thorax [21]- [24] and abdomen [21], [23], [25]. Diagonal mounting of RR sensors [9], [20] was also investigated.…”
Section: Introductionmentioning
confidence: 99%